Biodiversitas Fitoplankton di Waduk Selorejo, Kecamatan Ngantang Kabupaten Malang Jawa Timur - Suherman, Eman (Prosiding KPSDA, 2015)
The study of the biodiversity of phytoplankton in Selorejo dam was carried out of September 2014. The purpose of the study is to investigate the diversity of phytoplankton in Selorejo Dam. The methods used are drifting method and filtering method. The sample technique was taken once in four stations; two stations on drifting method and the other two stations for filtering method. This study was done with directly observation using binocular microscope in the laboratory of ecology. The data of water was retrieved that the temperature of waters is about 24-26o C, light intensity is 269 lux, the water colours are green and dark brownÂ with pH is 7. The result of study showed there are 4 species are that found from the same division, namely Chlorophyta consisting of Oedogonium sp, Stichococcus sp, Ankistrodesmus sp, and Spirogyra sp. As the eforts to keep the condition of water reservoirs in Selorejo need the handling variety of diversity to sustainability of phytoplankton that be one of bioindicator of waters quality.